Assessment of bacterial quality and shelf life pasteurized milk - Asha K (Department of Veterinary Public Health College of Veterinary and animal science, 2007)
In the present study raw and pasteurized milk samples were collected from two processing plants viz., DP1 and DP2 and pasteurized milk from retail shops. A total of 254 samples were analyzed for the bacterial quality by estimating various bacterial counts and also assessed the presence of certain bacteria of public health importance. The bacterial, physical and organoleptic qualities of pasteurized milk samples from two dairies stored under refrigeration (4 ± 1oC) were evaluated.